Pengembangan Game Edukasi Platformer Kisah Gajah Mada Menyatukan Nusantara Menggunakan Metode Iterative With Rapid Prototyping - Winny Ardhian Septiko; Muhammad Aminul Akbar; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
History is a record of the past about the changing in huma life. Every change in changes of history will provide a lesson for human life in the future. Similarly, what happens to life in Indonesia, every historical story that occurs in Indonesia has a high cultural values. One of them is the history of Majapahit Kingdom, wehere the history of Majapahit is one of the greatest historical stories and influences the life of Indonesian society, and the one is the story from The Journey of Gajah Mada to merge Indonesia in Majapahit, based on â€œSumpah Palapaâ€. But at the moment, the lack of public interest, especially children about its history, makes history a forgotten one. This is caused by learning media such as books, and lessons that tend to make students bored. In this research, the development of educational games about The Journey of Gajah Mada with a fun and interactive paltformer game for student. Testing results obtained by filling questionnaire by 20 respondents are calculated through Likert index interpretation. The results show that overall game is 81%, game view is 100%, the game rate is 83%, and the game difficulty level is 63%. And result of Usability Testing with SUS is 75,75. It's mean that the game is acceptable, on rating C and excellent rating. And get increase value from the test, it means that the game can be a education game media